Colorectal cancer: a multifaceted disease - Chun, Yun Shin; D’Angelica, Michael (Chinese Clinical Oncology; Vol 8, No 5 (October 09, 2019): Chinese Clinical Oncology (Molecular Markers in Colorectal Cancer), 2019)
We are pleased to present this focused issue on “Molecular Markers in Colorectal Cancer”. Advances in molecular profiling and bioinformatics have opened a frontier of exponentially increasing new knowledge that has accelerated the promise of precision oncology.